2020
DOI: 10.1037/pap0000276
|View full text |Cite
|
Sign up to set email alerts
|

Reflective awareness, repression, and the cognitive unconscious.

Abstract: The importance of reflective awareness for clinical practice is generally well recognized across a variety of therapeutic approaches. Psychodynamic approaches traditionally also recognize that defense mechanisms provide major impediments to reflective awareness. Recently, however, the neuropsychoanalyst Mark Solms proposes that the dynamic unconscious can be understood in terms of the nondeclarative cognitive unconscious. One consequence of Solms’ proposal is that there is no possibility of lifting repression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…For example, a belief would be described as descriptively unconscious if it was believed, without the person currently being aware of having the belief” (p. 2). He writes elsewhere that there is a difference between cognitive science's “cognitive unconscious” and the psychoanalytic “dynamic unconscious” (Boag, 2020 ). The former has non-motivated obstacles to becoming aware of something (e.g., automated processing that is implicit but not presently available to the mind while no motivated repression is involved).…”
Section: Psychoanalytic Contributions To the Distinctionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a belief would be described as descriptively unconscious if it was believed, without the person currently being aware of having the belief” (p. 2). He writes elsewhere that there is a difference between cognitive science's “cognitive unconscious” and the psychoanalytic “dynamic unconscious” (Boag, 2020 ). The former has non-motivated obstacles to becoming aware of something (e.g., automated processing that is implicit but not presently available to the mind while no motivated repression is involved).…”
Section: Psychoanalytic Contributions To the Distinctionmentioning
confidence: 99%
“…The former has non-motivated obstacles to becoming aware of something (e.g., automated processing that is implicit but not presently available to the mind while no motivated repression is involved). The latter has motivated obstacles preventing awareness (e.g., unconscious repression involving defense mechanisms defending against unprocessed pain) (Solms, 2017 , 2018 ; Boag, 2020 ).…”
Section: Psychoanalytic Contributions To the Distinctionmentioning
confidence: 99%
“…The theoretical models that analyze the narratives ( Pennebaker, 2000 ; Solano, 2013 ; Bucci, 2021a ) highlight how it is possible to understand the emotional organization and the structure of the person’s defenses during a particular moment in life. The autobiographical narrative capacity is closely linked to the use of defenses and the ability to stay in contact with the different emotions that the events of external and internal reality create in each of us ( Boag, 2020 ). For example, studies on the process of psychotherapy have shown how the progressive lowering of the ego’s defenses allowed for a greater awareness of one’s own experiences ( Kramer et al, 2020 ; De Roten et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%